Hash rearrangement scheme for HEVC screen content coding. Issue 4 (1st April 2018) - Kim, Ilseung; Jeong, Jechang
Abstract : This study presents a hash rearrangement scheme to improve coding efficiency of high‐efficiency video coding for screen content (HEVC‐SCC) by sharing hashes of the inter‐search with intra block copy (IBC). Of the various methods introduced during the HEVC‐SCC development, the IBC search technique can yield tremendous coding gains, but creates a massive computational burden on the encoder side. The authors propose an effective way to generate the IBC hash table to avoid redundant operations required for hash entry computation. Moreover, the authors propose a hash rearrangement scheme to apply the second hashes used in the inter‐search to IBC and the corresponding IBC search method to reduce the computational burden and to improve the coding efficiency. The experimental results show that compared with the HEVC‐SCC test model (SCM)‐8.0, the proposed algorithm results 80% time reduction when considering IBC hash generation itself, and can save 9–30% of hash generation time even taking into account the proposed second hash generation. It can also reduce the hash‐based IBC search time by 14.61%. Furthermore, the proposed algorithm can achieve Bjontegaard delta bit rate savings of −0.66, −0.45 and −0.66% on average for all intra, low‐delay, and random access coding structures, respectively.